Associations between waist circumference and executive function among Chinese Tibetan adolescents living at high altitude - Liu, Yuan; Zhang, Feng; Gan, Leimin; Shi, Lijuan; Yin, Xiaojian; Guo, Yaru; Sun, Pengwei (Frontiers in Nutrition, 2023)
Background: Associations between body composition and execution function (EF) were currently studied in low altitude (LA) areas. However, the research on the correlation between waist circumference (WC) and EF among adolescents living at high altitude (HA) was limited. Objective: We sought to explore the association between WC and EF in Chinese Tibetan adolescents aged 13–18 years in HA areas. Methods: After excluding invalid data and extreme values, 1228 participants (583 boys and 645 girls) were eventually included. The areas of Lhasa (average elevation of 3650 meters), Nagqu (4500 meters), Qamdo (3500 meters), and Nyingchi (3100 meters) in China were chosen as study sites. Participants completed tasks to measure inhibitory control, working memory, and cognitive flexibility. The predictive association between WC and EF was explored by One-way ANOVA, Pearson correlation, and linear regression analysis. Results: After adjustment for demographic indicators (gender, age, BMI, and site location), the reaction time (RT) of responding to congruent, incongruent, and homogeneous stimuli in subjects with WC ≥ 85th percentile was longer than that in those with WC of the 15th percentile or below ( by 32.275ms (95%CI: 12.063, 52.487), 32.840ms (95%CI: 12.885, 52.794), and 35.091ms (95%CI: 4.541, 65.641), respectively). After controlling for concomitant variables, WC was significantly positively correlated with the RT in the inhibitory control (incongruent) task, (P<0.05). However, after controlling for concomitant variables, WC was significantly negatively correlated with the RT in the working memory tasks (P<0.05). Conclusions: After adjustment for concomitant variables, WC was significantly associated with EF among Chinese Tibetan adolescents in HA areas.